The Relation Between Interest Congruence and College Major Satisfaction: Evidence From the Basic Interest Measures. (November 2019) - Bai, Lili; Liao, Hsin-Ya
The relation between the degree of interest congruence (i.e., person–environment fit in interest domain) and career satisfaction has been inconsistent and generally low across studies. Interest congruence is typically measured at the broadband general interest level, bound within Holland's Realistic, Investigative, Artistic, Social, Enterprising, and Conventional (RIASEC) framework, and largely based on the match of the high-point interest codes between persons and environments. Using two cross-cultural college samples, we reexamined the congruence–satisfaction relation with a refined congruence index by using narrowband basic interest measures and considering the entire basic interest profiles. As a comparison, we used three additional congruence indices based on the entire general interest RIASEC profiles or the high-point RIASEC codes. Findings showed stronger congruence–satisfaction relations when the basic interest measure and/or complete interest profiles were used to generate interest congruence indices. Implications for research and career practice are discussed.